2011
DOI: 10.1002/etc.617
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic and terrestrial stressors in amphibians: A test of the double jeopardy hypothesis based on maternally and trophically derived contaminants

Abstract: Amphibians with biphasic life histories occupy aquatic and terrestrial habitats at different times in their lives, leading to a double jeopardy of contaminant risk in both habitats. The present study examines individual and interactive effects of mercury exposure to terrestrial adults and aquatic larvae on fitness-related traits of American toads, Bufo americanus. Eggs from reference mothers or contaminated mothers were allowed to hatch and larvae were fed diets of either no added Hg or 2.5 or 10 µg/g total Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
(72 reference statements)
1
29
1
Order By: Relevance
“…Reference and contaminated mothers had total Hg (THg) concentrations of 159.5 ± 18.6 (mean ± SE hereafter) and 2,250 ± 489.8 ng/g ww in their blood, respectively (Todd et al 2011b). Reference and contaminated eggs had THg concentrations of 20.6 ± 1.3 and 149.1 ± 17.9 ng/g dw, respectively (Todd et al 2011b). Soon after hatching, larvae were allotted to dietary treatments and fed either control diet (0.01 ± 0.001 lg/g dw THg) or a diet spiked with environmentally relevant concentrations and proportions of inorganic and methyl-Hg (10.1 ± 2.3 lg/g THg dw, 1.05% monomethyl-Hg), creating four experimental crosses: (1) reference mothercontrol larval diet, (2) reference mother-Hg larval diet, (3) Hg mother-control larval diet, (4) Hg mother-Hg larval diet.…”
Section: Experimental Designmentioning
confidence: 96%
See 4 more Smart Citations
“…Reference and contaminated mothers had total Hg (THg) concentrations of 159.5 ± 18.6 (mean ± SE hereafter) and 2,250 ± 489.8 ng/g ww in their blood, respectively (Todd et al 2011b). Reference and contaminated eggs had THg concentrations of 20.6 ± 1.3 and 149.1 ± 17.9 ng/g dw, respectively (Todd et al 2011b). Soon after hatching, larvae were allotted to dietary treatments and fed either control diet (0.01 ± 0.001 lg/g dw THg) or a diet spiked with environmentally relevant concentrations and proportions of inorganic and methyl-Hg (10.1 ± 2.3 lg/g THg dw, 1.05% monomethyl-Hg), creating four experimental crosses: (1) reference mothercontrol larval diet, (2) reference mother-Hg larval diet, (3) Hg mother-control larval diet, (4) Hg mother-Hg larval diet.…”
Section: Experimental Designmentioning
confidence: 96%
“…Detailed methods and results of the earlier study on larvae are reported in Todd et al (2011b). Briefly, we acquired larvae from clutches of eggs from toads collected in either contaminated or uncontaminated portions of the South River floodplain near Waynesboro, VA, USA (Todd et al 2011b). Reference and contaminated mothers had total Hg (THg) concentrations of 159.5 ± 18.6 (mean ± SE hereafter) and 2,250 ± 489.8 ng/g ww in their blood, respectively (Todd et al 2011b).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations